시베리아 소수민족의 문화 변용: 시베리아횡단철도 주요 도시의 러시아화 - 임형백; Hyung-baek Lim (다문화와 평화, 2021)
이 논문은 시베리아횡단철도의 주요 도시의 러시아화를 고찰하였다. 러시아는 가장 영토가 넓은 국가이다. 시베리아는 러시아 전체 면적의 77%를 차지하고, 지구 전체 육지면적의 약 10%를 차지한다. 슬라브족은 기원후 450년과 550년 사이에 이르러서야 비로소 외부 세력의 압제에서 완전히 벗어났다. 우랄산맥은 아시아와 유럽의 경계를 형성한다. 16세기 중반까지 우랄산맥 동쪽은 원주민(소수민족)의 영토였다. 러시아의 우랄산맥 동쪽으로의 진출에는 카자크족의 역할이 컸다. 1581년에 조직된 동방원정대의 대장으로 기용된 예르마크 티모페예비치가 우랄산맥을 넘어 탐험을 시작한 이래, 원주민들의 감소와 문화파괴가 진행되는 반면, 러시아인의 이주와 문화전파가 이루어졌다. 카자크족은 여러 면에서 러시아의 확장에 기여했다. 1630년대 무렵 전염병 등으로 소수민족의 절반 이상이 사망했다. 17세기에 이르러 러시아는 태평양 연안에 다다랐다. 마지막 황제인 니콜라이 2세 때에 시베리아횡단철도를 건설하기 시작했다. 1891년 착공하여 1916년 개통되었다. 1년 뒤인 1917년에 러시아혁명이 일어났다. 1922년 공산주의 국가인 소련이 탄생했다. 이오시프 스탈린(1945-1953)은 1920년대 후반부터 숙청작업을 시작했다. 처음에 반대파 제거에서 출발한 숙청은 원주민에 대한 무차별 탄압으로 이어졌다. 1936년 스탈린 헌법은 “인종과 국적, 종교”뿐만 아니라, “사회적 출신, 재정적 지위, 과거 행동에 상관없는” 평등을 강제하였다. 소수민족의 말살이 시도되었고, 소수민족의 문화와 정체성은 많이 사라졌다. 스탈린의 러시아 민족주의는 유별났다. 하지만 그는 러시아 출신이 아닌 그루지야(현재의 조지아) 출신이었다. 러시아에는 약 120여 소수민족이 살고 있다. 소련은 볼셰비키의 민족해방과 민족자치에 대한 개념규정에 따라, 러시아인(슬라브족)이 소수인 지역, 즉 소수민족의 영역에 그 수와 비율에 따라 공화국, 자치공화국, 자치주 등을 구성했다. 소수민족들은 러시아혁명 이전부터 러시아인들로부터 탄압을 받아왔다. 러시아혁명 이후에는 소수민족의 정체성이 부정되었다. 이 과정에서 소수민족들의 거주지에 건설된 시베리아횡단철도의 주요도시들도 러시아인의 이주와 소련의 민족주의 정책에 따라 러시아화가 진행되었다. 이 논문은 대륙횡단철도의 주요 4개 노선, 시베리아횡단철도, 그리고 시베리아횡단철도가 통과하는 87개 도시 중에서, 연방관구의 주도, 인구 100만 이상의 수위 도시, 요충 도시 등을 고려하여 선정한 주요 11개 도시를 고찰하였다. 또 시베리아대평원에 대한 개요와 시베리아횡단철도의 개요를 고찰하였다. This paper examined the Russianization of major cities of the Trans-Siberian Railway. Russia is the most territorial country. Siberia occupies 77% of Russia's total land area and about 10% of the Earth's total land area. It was not until between A.D.450 and A.D.550 that the Slavs, to which the Russians belonged, were completely freed from external oppression. Until the middle of the 16th century, the eastern part of the Ural Mountains was the territory of a ethnic minorities. The Cossack played a major role in Russia's advance to the east of the Ural Mountains. The Cossack contributed to Russia's expansion in many ways. By the 1630s, more than half of the ethnic minorities died due to epidemics and other factors. By the 17th century, Russia had reached the Pacific coast. Construction of the Trans-Siberian Railway(TSR) began during the reign of the last emperor, Nicholas II. Construction began in 1891 and opened in 1916. A year later, in 1917, the Russian Revolution broke out. In 1922 the Soviet Union, a communist state, was born. Joseph Stalin (1945-1953) began purges in the late 1920s. The purge, which initially started with the elimination of opposition, led to indiscriminate oppression of ethnic minorities. The Stalin Constitution of 1936 enforced equality not only “race, nationality and religion” but also “regardless of social origin, financial status or past behavior”. Attempts were made to exterminate ethnic minorities, and the culture and identity of the ethnic minorities. Stalin's Russian nationalism was unusual. But he was not from Russia, but from Georgia. About 120 ethnic minorities live in Russia. In accordance with the Bolshevik concept of national liberation and national autonomy, the former Soviet Union constituted republics, autonomous republics, and autonomous territories according to the number and proportion in the area where Russians (Slavs) were a minority, that is, in the area of ethnic minorities. Ethic minorities have been oppressed by Russians even before the Russian Revolution. After the Russian Revolution, the identity of ethnic minorities was denied. In the process, major cities of the Trans-Siberian Railway built in the residences of ethnic minorities were also Russianized in accordance with the migration of Russians and the nationalist policy of the former Soviet Union. Among the four major transcontinental railway lines, the Trans-Siberian Railway, and the 87 cities through which the Trans-Siberian Railway passes, this thesis selected 11 major The city was examined. Also, in relation to the Trans-Siberian Railway, the outline of the Great Plains of Siberia and the Trans-Siberian Railway were reviewed.